Machinery manufacturing in Bangladesh : an industry study with particular reference to technological capability - Huq, M. Mozammel; Islam, K. M. Nabiul; Islam, Nazrul (Dhaka : University Press Limited, 1993)
Environment Management
Bibliography : p. 165-172
1996-04-24
Keywords: Mechinary; Industrial palnts; Techniques of production; Technology; Bangladesh